ASSESSMENT OF CRYPTOGRAPHIC KEY GENERATION SYSTEMS USING DREAD AND STRIDE THREAT METHODOLOGIES - Nurullaev , Mirkhon (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article presents a comprehensive assessment of cryptographic key generation systems using the DREAD and STRIDE threat methodologies. The article concludes by highlighting the importance of these methodologies for developing secure cryptographic systems and outlines future directions for refining threat models using real-world data and predictive analytics.